The Role of Social Media in Employee Recruitment and Selection - Hidayat, Deni Satriya (Universitas Negeri Yogyakarta, 2025)
The digital era has brought about fundamental changes in human resource management practices, particularly in employee recruitment and selection processes. This study examines these transformations through a comprehensive systematic literature review of 85 scientific articles published between 2010 and 2024. An in-depth analysis was conducted to explore how social media has reshaped the traditional recruitment landscape, as well as to identify opportunities and challenges in its implementation. The findings reveal that integrating social media into recruitment processes not only enhances operational efficiency but also introduces new dimensions in talent identification and evaluation. This study makes a significant contribution to understanding digital transformation in human resource management and presents a practical framework for effective implementation.